Executive functioning challenges of adolescents born extremely and very preterm - Lee, Samantha J.; Woodward, Lianne J.; Moor, Stephanie; Austin, Nicola C. (Frontiers in Psychology, 2024)
Background: Children born very preterm (VPT; <32 weeks) are at increased risk of executive functioning (EF) difficulties. But less is known about the nature and extent of these executive difficulties during late adolescence, particularly across multiple EF domains and in response to varying degrees of executive demand. Methods: Using data from a prospective longitudinal study, this paper describes the EF profiles of 92 VPT and 68 full-term (FT) adolescents at age 17 years. Relations between gestational age (GA) and later EF performance, in addition to neonatal predictors, were examined. Results: VPT-born adolescents performed less well than FT adolescents across the domains of working memory, planning, and cognitive flexibility, with the largest differences observed for those born <28 weeks GA (effect sizes -0.6 to -1.0 SD), and when task demands were high. The effects of GA on EF outcome were fully mediated by neonatal medical complexity (b = 0.169, t = -1.73) and term equivalent white matter abnormalities (b = 0.107, t = -3.33). Conclusion: Findings support the need for long-term cognitive support for individuals born very preterm, particularly those exposed to high levels of medical and neurological risk, with these factors largely explaining associations between GA and EF outcome.